Cooperation and Innovativity: the Network Foundations of the Regional System of Innovation - Csizmadia, Zoltán (Discussion Papers, 2012)
The regional process and the homogenous systemic architecture of innovation are embedded into the context of social contacts and their relevant networks which fundamentally determines their operation and efficiency. The problem is that on the different levels of the Hungarian environment of innovation we do not have exact information on the structures and mechanisms of their functional relationship. Putting in the simplest form of the major question of research sounds like that: ‘What kind of role do institutional contacts and their relevant networks play in a region’s capacity for innovation?’ The hypothesis is that the innovation processes of West-Transdanubia region are based on different type and purpose innovation cooperation systems grounded on social-institutional relations but functioning at a moderate intensity only. What are the reasons of this moderate intensity or absence of cooperation or expressing it in a more sophisticated way - of the random occurrence of cooperation? The most important conclusion is that the intensity of inter-firm cooperation has not increased in the last fifteen years in Hungary. The cooperation system is characterized by a low number of entirely bilateral connections and by the absence of complex development and innovation networks. Furthermore the majority of cooperation contacts are closed with partners operating in the economic/market sector.